Designing a digital portfolio - Baron, Cynthia (Berkeley, CA : New Riders, 2010)
From the Publisher: Portfolios have always been artists' most valuable tools for communicating their talents to the outside world, whether to potential employers or galleries or clients. But the days of sketches and slides have given way to arrangements of digital assets that are both simpler and more complex than their traditional analog counterparts. Instructor and design professional Cynthia Baron covers all the facets that artists need to know, from choosing the best work for a particular audience to using various file formats to organizing, designing, and presenting the portfolio. Beautiful full-color illustrations demonstrate her instructions and case studies throughout portray examples of attractive and effective portfolio design. This book gives artists at any level a creative edge, ensuring that their portfolios get noticed and help them stand out from the crowd.
8: Creating written content -- Avoiding writing errors -- What to write and why -- Identifying your work -- Introducing yourself -- Explaining your creative thinking -- Writing to your audience -- Portfolio highlight: Sandstrom Design -- Get your words' worth -- Part 3: Production -- 9: Structure and concept -- Choosing a delivery technology -- Developing for web or portable -- Thinking about structure -- Selecting a metaphor -- How you use a metaphor -- Concept -- Putting it all together -- Portfolio highlight: CloudRaker / Experienced design -- 10: Designing a portfolio interface -- Screen is not a book -- Interface design process -- Process stages -- Avoid distractions -- Moving to production -- Portfolio highlight: Layla Keramat / Master plan -- 11: Portfolio reels -- Reel possibilities -- Your reel and the market -- Developing the reel -- Structure -- Audience sweetners -- Reel delivery -- Portfolio highlight: Metaversal Studios / Reel life -- Part 4: Marketing -- 12: Copyright and portfolio -- Understanding fair use -- Respecting others' rights -- Roles and large projects -- Owning your work -- Protecting your work -- Protection technologies -- Dealing with infringement -- Portfolio highlight: Noa Studios / Fair share -- 13: Presenting your portfolio -- Testing your work -- Getting feedback -- Packaging a portable portfolio -- Getting the word out -- Contacting individuals -- Personal presentation -- Following up -- Staying relevant -- End, maybe -- Portfolio highlight: Ken Loh / Hand in the game -- Part 5: Appendixes -- Appendix A: Resources -- Appendix B: Contributors -- Index.
Previous ed.: 2004.
Includes bibliographical references and index.
Keywords: Art portfolios -- Design; Graphic arts -- Marketing; Design services -- Marketing; Computer graphics; Internet marketing; Computer graphics; Multimedia; Art -- Marketing